Framed: Astonishing True Stories of Wrongful Convictions : Astonishing True Stories of Wrongful Convictions - Grisham, John; McCloskey, Jim, (Minister) (New York : Doubleday, 2024)
"In his first work of nonfiction since The Innocent Man, #1 bestselling author John Grisham and Centurion Ministries Founder Jim McCloskey share ten harrowing true stories of wrongful convictions. Impeccably researched and grippingly told, Framed offers an inside look at the victims of the United States criminal justice system. A fundamental principle of our legal system is a presumption of innocence, but once someone has been found guilty there is very little room to prove doubt. Framed shares ten true stories of men who were innocent but found guilty and forced to sacrifice friends, families, wives, and decades of their lives to prison while the guilty parties remained free. In each of the stories, John Grisham and Jim McCloskey recount the dramatic hard-fought battles for exoneration. They take a close look at what leads to wrongful convictions in the first place, and the racism, misconduct, flawed testimony, and the corrupt court system that can make them so hard to reverse. Told with page-turning suspense as only John Grisham can deliver, Framed is the story of overcoming adversity when the battle already seems lost, and the deck is stacked against you"--.
"This slipcased edition of Framed is limited to 175 copies, numbered and signed by the authors. This is copy 43".
new book 2025 spring.
Keywords: Judicial error -- United States; Criminal justice, Administration -- United States; Racism in criminal justice administration -- United States; Discrimination in criminal justice administration -- United States